ROOT CAUSES OF AGRICULTURAL MINERAL SOILS DEGRADATION AND POSSIBILITY OF IMPLEMENTATION OF EXPRESS-METHOD OF MONITORING AND MANAGEMENT OF SOIL FERTILITY - Kozishkurt, Svitlana; Kozishkurt, Andrii; Olіinуk Oksana (Вісник Національного університету водного господарства та природокористування. Серія «Сільськогосподарські науки», 2020)
The substantiations and formulations, given in the work, will provide a regular and detailed supervision of the dynamics of agro-physical properties of soils; they will also allow accelerating and simplifying of the determination of a number of agrohydrologic properties of the soil; besides, they will allow correction of agroameliorative measures for improvement of soil ecological stability at their agricultural use. It is well-known that excessive mechanical soil cultivation, application of heavy agricultural and ameliorative machinery, significant mineral fertilization and insufficient organic fertilizers application, application of pesticides and nonobservance of soil conservation technologies caused deterioration of agrohydrological properties of soils, loss of humus and compaction of root habitable layer. As a result, the qualitative and quantitative changes of structure take place in the soils and water-air and thermal regimes of the root habitable layer and conditions of plants nutrition deteriorate. The processes of waterlogging, salinization, solonetization, depletion of peat and etc. are observable on the ameliorated lands. The soil compaction degree also depends on other factors, and first of all, on granulometric composition and degree of the soil humidity at its cultivation time. Namely those factors determine the potential soil resistance to deformation. Humid soils having heavy granulometric composition become more compact and dry soils having light composition become less compact. The results of field studies of 6 soil profiles of the lands from different districts of Chernihiv region were collected and used in order to determine the correlation dependence between the density and agrohydrological properties of soils. The data of density, soil skeleton density, total soil porosity, maximum and minimum water holding capacity and withering point were used for search of the correlation ratio. By means of regression equation with high correlation coefficient the absence of any connection between the density and specific gravity of the soil solid part was detected. Such agrohydrological properties of soils as maximum and minimum water holding capacity and total soil porosity change when the density changes. A close connection was determined by means of regression equations. It allows us to speak about the possibility of implementation of the method of determination of the majority of indexes of soils agrohydrological properties according to the values of density of the soils into the agroameliorative praxis.